EXERCISE REDUCE OXIDATIVE DAMAGE IN PREGNANCY - Wagey, F. W; Pangkahila, A.; Surya, I.G.P; Bagiada, A (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 5, No. 2 Mei 2011)
Pregnancy is a vulnerable condition to all kinds of "stress", resulting in changes of physiological and metabolic functions. This research aims to determine effect of exercise during pregnancy in reducing oxidative demage marked by decrease of malondialdehyde and 8-hydroxy-diguanosine levels. Randomized pre and posttest control group design was employed in this study. A number of 66 pregnant women were recruited in this study and grouped to two groups, i.e 30 of them as control group and the rest as treatment group. Pregnancy exercise was performed to all 36 pregnant women from 20 weeks gestation on treatment group. The exercise was performed in the morning for about 30 minutes, twice a weeks. On the other hand, daily activities was sugested for control group. Student’s t-test was then applied to determine the mean different of treatment and control group with 5 % of significant value. This study reveals that there were significantly higher decrease of (MDA) and 8-OHdG about 0.15 nmol/ml and 0.08 ng/ml, respectively, amongs treatment and control groups (p < 0.05). Clinical outcomes, such as strengten of pelvic muscle and quality of life of treatment group were significantly better compared to control group (p < 0.05). This means that exercise during pregnancy ages of 20 weeks decrease MDA and 8-OHdG levels higher compare to control group without exercise.
Keywords: oxidative stress, malondialdehyde, 8-hidroxy-2-deoxy-diguanosine,